Impedimetric Immunosensor for On-Site Measurement of Rituximab from Invasive and Non-Invasive Samples. Issue 5 (1st May 2022) - Batista Rodrigues, Edson Silvio; Mello e Silva, Giovanna Nascimento de; Macêdo, Isaac Yves Lopes de; Pio dos Santos, Wallans Torres; Souza, Guilherme Rocha Lino de; Santos, Gabriel Henrique; Wastowski, Isabela Jubé; Ates, Hatice Ceren; Dincer, Can; Gil, Eric de Souza
Abstract : Rituximab (RTX) is a specific monoclonal antibody for CD20 protein, which are mostly found in lymphocytes B. RTX is notably indicated for lymphomas, autoimmune disorders, leukemia and transplant rejections. A higher efficiency is achieved by adjusted doses, which is tailored by individual body weight and RTX pharmacokinetic parameters. Therefore, the individualized dosing is a usual practice to achieve the therapeutic success of this expensive drug. Therapeutic monitoring of RTX is commonly performed by chromatographic methods or immunoassays. These methods, however, suffer from lack of standardization in workflows, long turnaround times and high instrumentation costs with complex sample preparation. In this regard, immunosensors emerge as a feasible alternative to overcome these limitations. Herein, we developed an impedimetric immunosensor, which can detect RTX from both invasive and non-invasive samples, in this way our immunosensor is applicable in blood plasma and urine samples allowing a new analysis approach. A linear correlation between the charge transfer resistance and RTX from 2 to 14 μ g ml −1 (r 2 of 0.99) along with limit-of-detection and limit-of-quantification of 130 and 400 ng ml −1, respectively, was obtained. The immunosensor implemented proved to have sufficient precision and accuracy for on-site RTX detection in both blood serum and urine samples. Such affordable, label-free and highly sensitive electrochemical immunosensors could pave the way for on-site therapeutic drug monitoring, quality control and extended stability monitoring of different drugs, in a simple manner along with short turnaround times and low costs.